Power system state estimation implementation - Zhang, ZheXin. (2012)
This project is to suitable for student with an interest in power system analysis to understand the concept behind power system state estimation. The student will be tasked to develop a suitable state estimation algorithm using tools such as Matlab to implement and test the state estimator's performance using appropriate data set.